Silver-coated versus uncoated locking plates in subjects with fractures of the distal tibia: a randomized, subject and observer-blinded, multi-center non-inferiority study - Schoder, S.; Lafuente, M.; Alt, V. (Current controlled trials in cardiovascular medicine, 2022)
Antimicrobial coatings of implants are of interest to reduce infection rate in orthopedic surgery. Demonstration of clinical effectiveness of such coated implants to obtain market approval is challenging. The objective of this article is to define a design for a randomized controlled trial to evaluate the clinical performance of a silver-coating for locking plates for fracture treatment. The study design has to respect different criteria, such as feasibility, focus on overall complications, such as functional impairment, fracture healing, and particularly on infection rates. Distal tibia fractures were chosen due to the high prevalence of infections in this type of injuries, which warrants a particular benefit of antimicrobial prophylaxis and thus might allow to see a statistical trend in favor of the coated product. The study design was defined as a randomized, controlled, subject and observer-blinded, multi-center study in subjects with fractures of the distal tibia with a total of 226 patients. A number of 113 patients are planned for each of the two treatment arms with treatment of the fracture with a silver-coated device (first arm) or with an uncoated device (second arm). Inclusion criteria are closed fractures of the distal tibia according to the Tscherne-Oestern classification or open fractures of the distal tibia according to the Gustilo-Anderson classification in subjects older than 18 years. Primary outcome parameter is the Anticipated Adverse Device Effects (AADE) including all typical complications of this type of injury, such as functional impairment of the affected limb, non-union, and infections based on a non-inferiority study design. Also, silver-typical complications, such as argyria, are included. Secondary parameters are infection rates and fracture healing. Follow-up of patients includes five visits with clinical and X-ray evaluations with a follow-up time of 12 months. Demonstration of clinical effectiveness of antimicrobial coatings of fracture fixation devices remains a challenge. Definition of a prospective randomized pre-market trial design and recruitment of clinical sites for such a study is possible. A confirmative proof of the expected clinical benefit in terms of reduction of device-related infections will be addressed with a prospective post-market clinical follow-up study in a second step due to the large sample size required. ClinicalTrials.gov NCT05260463. Registered on 02 March 2022.